2000
DOI: 10.1074/jbc.275.16.11721
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Function of RANTES, MIP-1α, and MIP-1β following Interaction with Heparin-like Glycosaminoglycans

Abstract: Chemokines are a group of small proteins that have a variety of functions, including the activation and recruitment of immune cells during episodes of inflammation. In common with many cytokines, it has been observed that chemokines have the potential to bind heparin-like glycosaminoglycan molecules, which are normally expressed on proteoglycan components of the cell surface and extracellular matrix. The significance of this interaction for chemokine activity remains a subject of debate. In this study, Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 37 publications
4
103
0
3
Order By: Relevance
“…The association of chemokines with GAGs of the extracelluar matrix and on the cell surface has important implications in terms of presentation and increasing local chemokine levels. Using GAG deficient Chinese hamster ovary cells transfected with CCR1 and CCR5, Ali et al [17] demonstrated that surface GAGs increase the concentration of chemokines presented to the CCRs at the molecular level. CCL5 has been shown to bind GAGs with distinct specificity [16] suggesting that CCL5 may be crucial in mediating inflammatory responses.…”
Section: Chemokines Are (Co)stimulatory For T Cellsmentioning
confidence: 99%
“…The association of chemokines with GAGs of the extracelluar matrix and on the cell surface has important implications in terms of presentation and increasing local chemokine levels. Using GAG deficient Chinese hamster ovary cells transfected with CCR1 and CCR5, Ali et al [17] demonstrated that surface GAGs increase the concentration of chemokines presented to the CCRs at the molecular level. CCL5 has been shown to bind GAGs with distinct specificity [16] suggesting that CCL5 may be crucial in mediating inflammatory responses.…”
Section: Chemokines Are (Co)stimulatory For T Cellsmentioning
confidence: 99%
“…5,47 A variety of experiments have shown that GAG are critically important for chemokine activity, 3,5,23,48 with loss of cell surface heparan sulfate severely limiting chemokine activity. 34,42,49 Soluble chemokine concentration gradients have been shown to direct immune cell migration in vitro. During inflammation in vivo, it is likely that chemokines produced by subendothelial tissues contribute to the recruitment of blood-borne leukocytes following redistribution and presentation on the apical surface of the endothelium.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinmentioning
confidence: 99%
“…1). The quaternary structures of chemokines vary dramatically within the superfamily, with a range of monomeric, dimeric, and tetrameric structures seen, although there is convincing evidence that the monomer is sufficient for receptor activation (19,20). The three-dimensional structures of eotaxin (21), eotaxin-2 (22), and eotaxin-3 2 have recently been determined and are all monomeric.…”
mentioning
confidence: 99%